Centres of research excellence in economics in the Republic of Ireland - Ruane, Frances; Tol, Richard S.J. (Economic & Social Studies, 2007)
Using publication, citation and h-numbers from the Scopus and Web of Science databases, we find that research output and academic influence of economists in the Republic of Ireland are heavily skewed by researcher and by institution. A subset of the results is confirmed by similar analyses based on EconLit, Google Scholar and IDEAS/REPEC. The analysis shows that while one university dominates in terms of numbers of economists, the more productive and most cited Irish research economists are spread across a range of institutions that are heavily concentrated in the Greater Dublin Area.
Keywords: Economics research; Research institutes; Ireland